Science Literacy Assessment Instrument for Additives and Addictive Substances: Development, Validation, and Rasch Model Analysis - Syarif Faisal; Ani Rusilowati; Endang Susilaningsih (Jurnal Penelitian Pendidikan IPA, 2023)
Science literacy is one of the areas of basic literacy that PISA focuses on. Science literacy is essence of learning in the 21st century. The purpose of this study is to develop and validate instruments to assess science literacy in the area of additives and addictive substances. The researcher refers to the modified PISA framework and Bloom's Revised Taxonomy. The developed instrument was tested for reliability and validity using the Aiken V method and the Rasch model. The research respondents consisted of 47 students from two junior high schools: a public school and a private school that has been accredited A. The results of the analysis showed that the instrument has validity. The results of the analysis showed that of the 25 items given there were 24 valid items, the resulting Cronbach's alpha value of 0.86 showed very good criteria, it can be concluded that the instrument has high validity and good reliability. This instrument is expected to be used to measure the quality of education and science literacy of students in Indonesia.